I’m okay, you’re not okay: Constancy of character and Paul’s understanding of change in his own and Peter’s behaviour - Eric Stewart (HTS Teologiese Studies/Theological Studies, 2011)
Paul argues in Galatians 2:11–14 that Peter was guilty of hypocrisy because he had withdrawn from eating with Gentiles in Antioch. Paul’s argument is best understood through the social and rhetorical conventions related to the encomium. The problem for Paul is that his own behaviour is inconsistent, and the Galatians know of his changed behaviour (Gl 1:13). Paul, then, is at pains to explain how his own changed behaviour, as a result of a commissioning from God, is different from Peter’s changed behaviour, as a result of fear of those from the circumcision. Paul’s concern for explaining his own change in behaviour as positive and Peter’s as negative is related to his overall concern to prevent future changes in the Galatians’ behaviour given that they are, as Paul himself is, commissioned by God for a new freedom.